SELECTION OF SOFT CLAY PARAMETERS FOR BANGKOK LOWLAND DEVELOPMENT - A. S. Balasubramaniam; S. R. Kim; D. G. Lirr; S. S. S. Acharya; T. H. Seah; D. T. Bergado (Lowland Technology International, 1999)
The paper stresses the importance of a sound understanding of the soil behaviour in both the limit equilibrium and numerical analysis in soil- structure interaction problems: deep foundation for tall buildings; foundation for elevated expressways, subways, ground improvements works, tunnels for water supply, natural gas supply, sewerage and drainage. In the limit equilibrium analysis the use of Hvorslev strength parameters is suggested while for lightly overconsolidated clays the strength to be referred as a frictional component. In the numerical analysis a realistic stress- strain model for the behaviour of soft clays for stress states below the state boundary surface is recommended.